The both positive and negative effect of pre-strain on the mechanical response of extruded magnesium alloy - Abdul Malik (Elsevier, 2021)
The Mechanical response of magnesium alloy is highly dependent on the texture especially in extruded magnesium alloys. Here in this study pre-compression was applied up to different strain levels and its effect on the stress-strain response has been observed. Our result illustrated that the pre-compression increased compressive yield strength, ultimate compression strength and ultimate tensile strength; however the tensile yield strength was significantly decreased.